Social Networks and Obesity - Kellie Cooper; Megan A. McVay; LaToya J. O'Neal (EDIS)
Social networks play a very important part in successful weight management. This publication discusses social networks and ways these connections may support or hinder weight management. Written by Kellie Cooper, Megan A. McVay, and LaToya J. O’Neal, and published by the UF/IFAS Department of Family, Youth and Community Sciences, September 2022.